2016
DOI: 10.1002/1873-3468.12072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of differential pore‐forming activities of ESAT‐6 proteins from Mycobacterium tuberculosis and Mycobacterium smegmatis

Abstract: Mycobacterium tuberculosis ESAT-6 (MtbESAT-6) plays essential roles in pathogenesis. MtbESAT-6 exhibits a unique pore-forming activity (PFA) that is not found in its ortholog from non-pathogenic Mycobacterium smegmatis (MsESAT-6). Here we characterized the differential PFAs and found that exchange of I25-H26/T25-A26 between two proteins reciprocally affected their PFAs. MtbESAT-6(IH/TA) had ~40% reduction, while MsESAT-6(TA/IH) fully acquired its activity similar to MtbESAT-6. Mutations of A17E, K38T, N67L or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 56 publications
3
32
1
Order By: Relevance
“…Rather, we find that the various lytic activities attributed to ESAT-6 at neutral pH are the result of a widely used protocol to isolate ESAT-6, which leaves residual detergent in the preparations. We find that detergent-free ESAT-6 preparations can disrupt liposomes under acidic conditions, as previously observed (25,27,28). However, this intrinsic low pHdependent activity of ESAT-6 is not responsible for mycobacterial phagosomal permeabilization in host macrophages.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Rather, we find that the various lytic activities attributed to ESAT-6 at neutral pH are the result of a widely used protocol to isolate ESAT-6, which leaves residual detergent in the preparations. We find that detergent-free ESAT-6 preparations can disrupt liposomes under acidic conditions, as previously observed (25,27,28). However, this intrinsic low pHdependent activity of ESAT-6 is not responsible for mycobacterial phagosomal permeabilization in host macrophages.…”
supporting
confidence: 85%
“…Prior work had suggested that ESAT-6 mediated ESX-1 membrane lytic activity through pore-forming activity (15,18,28,34). If so, mycobacterial culture supernatants should produce hemolysis.…”
Section: Resultsmentioning
confidence: 99%
“…These initial biophysical data were extended by several independent reports, including those demonstrating EsxA-dependent lysis of physiologically relevant liposome membranes (177), characterizing pore formation in sheep red blood cell (sRBC) membranes by EsxA (53), and the lysis of type 1 and type 2 pneumocytes by either purified EsxA or EsxA applied to the surface of ESX-1-deficient mycobacterial strains (167). Several more recent studies have focused on the mechanism of EsxA membrane lysis by investigating changes to membrane lysis as a function of pH (177), by comparing the activities of EsxA proteins from pathogenic and nonpathogenic mycobacterial species (178,179), and by generating specific point mutations which disrupt the membranolytic activity of EsxA (180). For a recent comprehensive review of the evidence of EsxA pore-forming activity, please see the study by Peng and Sun (181).…”
Section: Esx-1 a Membranolytic Systemmentioning
confidence: 99%
“…Coupled with evidence that ESX-1 substrates are present in the capsule and on the cell surface, discovered by our group and several others, direct translocation of ESX-1 substrates into the host macrophage may not occur. Rather, the presence of ESX-1 substrates on the cell surface may be sufficient for promoting phagosomal lysis (134,(166)(167)(168)(169)(170)(171)(172)(173)(174)(175)(176)(177)(178)(179)(180)(181)(182)(183)(184)(185). Alternatively, contact with membranes may induce ESX-1 secretion through an unknown signal transduction mechanism.…”
Section: Esx-1 a Membranolytic Systemmentioning
confidence: 99%
“…This discrepancy between native and recombinant proteins could be explained by mycobacterium-specific post-translational modifications on ESAT6 [52]. Both recombinant and native ESAT6 lyse artificial membranes [59,[61][62][63][64] due to a hypothetical conformational change of ESAT6 that also facilitated membrane interaction [61]. The helix-turn-helix structure of ESAT6 was shown to insert into membranes upon acidification and to form a membrane-spanning structure, which could lead to membrane lysis [65].…”
Section: Transport Across Membranes Esx-1 Secretion and Esat6mentioning
confidence: 99%